A Potent Soluble Epoxide Hydrolase Inhibitor, t-AUCB, Acts Through PPARγ to Modulate the Function of Endothelial Progenitor Cells From Patients with Acute Myocardial Infarction - Xu, Dan-yan (2012)
BACKGROUND: Epoxyeicosatrienoic acids (EETs) are natural angiogenic mediators regulated by soluble epoxide hydrolase (sEH). Inhibitors of sEH can stabilize EETs levels and were reported to reduce atherosclerosis and inhibit myocardial infarction in animal models. In this work, we investigated wether increasing EETs with the sEH inhibitor t-AUCB would increase angiogenesis related function in endothelial progenitor cells (EPCs) from patients with acute myocardial infarction (AMI). METHODS AND RESULTS: EPCs were isolated from 50 AMI patients and 50 healthy subjects (control). EPCs were treated with different concentrations of t-AUCB for 24 hours with or without peroxisome proliferator activated receptor γ (PPARγ) inhibitor GW9662. Migration of EPCs was assayed in trans-well chambers. Angiogenesis assays were performed using a Matrigel-Matrix in vitro model. The expression of vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1α (HIF-1α) mRNA and protein in EPCs were measured by real-time PCR or Western blot, respectively. Also, the concentration of EETs in the culture supernatant was detected by ELISA. The activity of EPCs in the AMI patient group was reduced compared to healthy controls. Whereas increasing EET levels with t-AUCB promoted a dose dependent angiogenesis and migration in EPCs from AMI patients. Additionally, the t-AUCB dose dependently increased the expression of the angiogenic factors VEGF and HIF-α. Lastly, we showed that these effects were PPARγ dependent. CONCLUSION: The results demonstrate that the sEH inhibitor positively modulated the functions of EPCs in patients with AMI through the EETs-PPARγ pathway. The present study suggests the potential utility of sEHi in the therapy of ischemic heart disease.